ENVIRONMENTAL PROBLEMS IN URBAN AREAS OF THE WILAYA OF BATNA: EXAMPLES FROM THE SOUTH-EASTERN AREA - Sabri Sayed Elleithi Shaima; Redjal Omar; Meddour Oualid (International Journal of Innovative Technologies in Social Science, 2024)
The state’s efforts to improve the living conditions of the population in the Aures region have been, and continue to be, aimed at reducing disparities to achieve balance among the various regions of the country. Housing and infrastructure are among the most important mechanisms it has relied upon to stabilize the population and develop their areas. Despite the efforts made, the desired goals have not been achieved due to a lack of consideration for the specific characteristics of these mountainous regions, particularly their natural, urban, cultural, and social aspects, which have contributed to the development of these rural areas. The combination of natural, historical, political, economic, and demographic factors and circumstances contributed to the development of population clusters in the study area. (Oued Abdi and Oued El Abiod regions - Aures). According to a field study based on a comparison between different study centers, relying on data sourced from investigations and observations we conducted with the residents and various relevant authorities, we highlighted the transformations that the region has experienced, which have led to environmental repercussions. We examined the mechanisms involved and the various actors in these fragile mountainous areas, and then we attempted to present the levels of environmental degradation in the region and identify the different issues facing these areas. In conclusion, we highlighted the most important mechanisms through which we can protect the environment in mountainous areas, and we emphasized the necessity of taking the required measures in various fields, especially urban, forest, and agricultural, to achieve sustainable mountain development a “sustainable mountainous area”.